Human Cell-Based Micro Electrode Array Platform for Studying Neurotoxicity - Ylä-Outinen, Laura; Heikkilä, Juha; Skottman, Heli; Suuronen, Riitta; Äänismaa, Riikka; Narkilahti, Susanna (Frontiers in Neuroengineering, 2010)
At present, most of the neurotoxicological analyses are based on in vitro and in vivo models utilizing animal cells or animal models. In addition, the used in vitro models are mostly based on molecular biological end-point analyses. Thus, for neurotoxicological screening, human cell-based analysis platforms in which the functional neuronal networks responses for various neurotoxicants can be also detected real-time are highly needed. Microelectrode array (MEA) is a method which enables the measurement of functional activity of neuronal cell networks in vitro for long periods of time. Here, we utilize MEA to study the neurotoxicity of methyl mercury chloride (MeHgCl, concentrations 0.5-500 nM) to human embryonic stem cell (hESC)-derived neuronal cell networks exhibiting spontaneous electrical activity. The neuronal cell cultures were matured on MEAs into networks expressing spontaneous spike train-like activity before exposing the cells to MeHgCl for 72 hours. MEA measurements were performed acutely and 24, 48, and 72 hours after the onset of the exposure. Finally, exposed cells were analyzed with traditional molecular biological methods for cell proliferation, cell survival, and gene and protein expression. Our results show that 500 nM MeHgCl decreases the electrical signaling and alters the pharmacologic response of hESC-derived neuronal networks in delayed manner whereas effects can not be detected with qRT-PCR, immunostainings, or proliferation measurements. Thus, we conclude that human cell-based MEA-platform is a sensitive online method for neurotoxicological screening.